Polariton propagation in shallow-confinement heterostructures: Microscopic theory and experiment showing the breakdown of the dead-layer concept - Schumacher, Stefan; Czycholl, G.; Jahnke, F.; Kudyk, I.; Rückmann, H. I.; Gutowski, J.; Gust, A.; Alexe, G.; Hommel, D. (Physical Review B)

Coherent propagation of polaritons in semiconductor heterostructures: Nonlinear pulse transmission in theory and experiment - Schumacher, Stefan; Czycholl, G.; Jahnke, F.; Kudyk, I.; Wischmeier, L.; Rückmann, I.; Voss, T.; Gutowski, J.; Gust, A.; Hommel, D. (Physical Review B)

Quasiparticle bands and optical spectra of highly ionic crystals: AlN and NaCl - Bechstedt, F.; Seino, K.; Hahn, P. H.; Schmidt, Wolf Gero (Physical Review B)

Understanding the optical anisotropy of oxidized Si(001) surfaces - Fuchs, F.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Second-harmonic polarizability including electron-hole attraction from band-structure theory - Leitsmann, R.; Schmidt, Wolf Gero; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Optical response ofπ-conjugated molecular monolayer adsorbed on the semiconductor Si(001) surface: A first-principles study - Hermann, A.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Molecular electronic excitations calculated from a solid-state approach: Methodology and numerics - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Excitonic wave packet dynamics in semiconductor photonic-crystal structures - Pasenow, B.; Reichelt, Matthias; Stroucken, T.; Meier, Torsten; Koch, S. W. (Physical Review B)
Significant aspects of the light–matter interaction can be strongly modified in suitably designed systems consisting of semiconductor nanostructures and dielectric photonic crystals. To analyze such effects, a microscopic theory is presented, which is capable of describing the optoelectronic properties of such hybrid systems via a self-consistent solution of the dynamics of the optical field and the photoexcitations of the material. The theory is applied to investigate the local excitonic resonances, which arise as a consequence of the modified Coulomb interaction in the vicinity of a structured dielectric medium. The excitation of a coherent superposition of the spatially inhomogeneous optical transitions induces an intricate wave packet dynamics. In the presence of dephasing and relaxation processes, the coherent oscillations are damped and the photoexcited carriers relax into spatially inhomogeneous quasi-equilibrium distributions.

Nonlinear optical response of the Si ( 111 ) − ( 2 × 1 ) surface exciton: Influence of biexciton many-body correlations - Oszwałdowski, R.; Reichelt, Matthias; Meier, Torsten; Koch, S. W.; Rohlfing, Michael (Physical Review B)

Time-resolved photoluminescence of type-I and type-II (GaIn) As/Ga (NAs) heterostructures - Hantke, K.; Heber, J. D.; Schlichenmaier, C.; Thränhardt, A.; Meier, Torsten; Kunert, B.; Volz, K.; Stolz, W.; Koch, S. W.; Rühle, W. W. (Physical Review B)
A set of (Ga0.77In0.23)As/Ga(NxAs1−x) heterostructures is studied by time-resolved photoluminescence. Four samples with nitrogen concentrations from x=0.48% up to x=2.2% are investigated at different temperatures and with different excitation densities. The experiments suggest that the heterostructure band offset is type I for x=0.48% and type II for x=2.2%. The situation is more complex for x=0.72% and x=1.25%, since these samples are close to the transition from type I to type II. The experimental findings are analyzed using a detailed microscopic theory. Numerical calculations describe the measured data well. In particular, the interpretation of the experimental results concerning the band alignment is confirmed by the theoretical analysis.

Spatially inhomogeneous optical gain in semiconductor photonic-crystal structures - Reichelt, Matthias; Pasenow, B.; Meier, Torsten; Stroucken, T.; Koch, S. W. (Physical Review B)
The optical and electronic properties of semiconductor heterostructures in the vicinity of photonic crystals are discussed. The theoretical approach provides a self-consistent solution of the dynamics of the electromagnetic field and the material excitations. Due to the influence of the structured dielectric environment on the Coulomb interaction, the exciton resonances and the quasiequilibrium carrier densities in the spatially homogeneous semiconductor become space dependent. It is demonstrated that these inhomogeneities lead to distinct modifications of the optical absorption and gain spectra. As an application, numerically calculated density-dependent optical spectra are analyzed for an array of semiconductor quantum wires which are close to a two-dimensional photonic crystal. The spatial inhomogeneities result in novel excitonic absorption features and modification of the optical gain in these structures.

Optical properties of planar metallic photonic crystal structures: Experiment and theory - Christ, A.; Zentgraf, Thomas; Kuhl, J.; Tikhodeev, S. G.; Gippius, N. A.; Giessen, H. (Physical Review B)

Control of fine-structure splitting and biexciton binding inInxGa1−xAsquantum dots by annealing - Langbein, W.; Borri, P.; Woggon, U.; Stavarache, V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Radiatively limited dephasing in InAs quantum dots - Langbein, W.; Borri, P.; Woggon, U.; Stavarache, V.; Reuter, Dirk; Wieck, A. (Physical Review B)

Two relaxation mechanisms observed in transport between spin-split edge states at high imbalance - Deviatov, E. V.; Würtz, A.; Lorke, A.; Yu. Melnikov, M.; Dolgopolov, V. T.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Adiabatically driven electron dynamics in a resonant photonic band gap: Optical switching of a Bragg periodic semiconductor - Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Prineas, John P.; Nielsen, Nils C.; Kuhl, Jürgen; Khitrova, Galina; Gibbs, Hyatt M.; Giessen, Harald; Koch, Stephan W. (Physical Review B)
The adiabatic driving of the resonant electron dynamics in a one-dimensional resonant photonic band gap is proposed as an optical mechanism for nonlinear ultrafast switching. Pulsed excitation inside the photonic gap results in an ultrafast suppression and recovery of the gap. This behavior results from the adiabatic carrier dynamics due to rapid radiative damping inside the band gap.
Keywords: tet_topic_qw

Linear and nonlinear pulse propagation in a multiple-quantum-well photonic crystal - Nielsen, N. C.; Kuhl, J.; Schaarschmidt, M.; Förstner, Jens; Knorr, A.; Koch, S. W.; Khitrova, G.; Gibbs, H. M.; Giessen, H. (Physical Review B)
We investigate the temporal and spectral properties of subpicosecond pulses transmitted on the heavy-hole exciton transition through a multiple-quantum-well Bragg structure, exhibiting a one-dimensional photonic band gap. At low light intensities, a temporal propagation beating is observed. This beating is strongly dependent on the optical dephasing time T2 which is dominated by the radiative interwell coupling. In an intermediate intensity regime, the Pauli-blocking nonlinearity leads to gradual suppression of the photonic band gap and vanishing of the linear propagation beating. For highly nonlinear excitation, we find signatures of selfinduced transmission due to Rabi flopping and adiabatic following of the carrier density. Numerical simulations using the semiconductor Maxwell-Bloch equations are in excellent agreement with the experimental data up to intensities for which higher many-particle correlations become more important and self-phase modulation occurs in the sample substrate.
Keywords: tet_topic_qw

Optical dephasing of coherent intersubband transitions in a quasi-two-dimensional electron gas - Waldmüller, I.; Förstner, Jens; Lee, S.-C.; Knorr, A.; Woerner, M.; Reimann, K.; Kaindl, R. A.; Elsaesser, T.; Hey, R.; Ploog, K. H. (Physical Review B)

Organic modification of surface electronic properties: A first-principles study of uracil on Si(001) - Seino, K.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

X-ray absorption and magnetic circular dichroism studies of ion-bombarded ferromagnet-antiferromagnet bilayers - Schmalhorst, J.; Sacher, Marc; Höink, V.; Reiss, G.; Engel, D.; Ehresmann, A. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

X-ray absorption and magnetic circular dichroism studies of ion-bombarded ferromagnet-antiferromagnet bilayers - Schmalhorst, J.; Sacher, Marc; Höink, V.; Reiss, G.; Engel, D.; Ehresmann, A. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Interface structure and magnetism of magnetic tunnel junctions with aCo2MnSielectrode - Schmalhorst, J.; Kämmerer, S.; Sacher, Marc; Reiss, G.; Hütten, A.; Scholl, A. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials